Synthesis and characterization of DyxCoFe2-xO4 nanoparticles - Kumar, Hemaunt; Singh, Jitendra Pal; Srivastava, R. C.; Patel, K. R.; Chae, Keun Hwa (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2017)
In the present work, we report the synthesis of Dy doped CoFe2O4 nanoparticles using chemical method. Doping of Dy ions upto 0.15 in the host lattice does not result into impurity phase as revealed from X-ray diffraction (XRD) and Raman spectroscopy measurments. Near edge X-ray absorption fine structure measurments show the modification of Fe(3d)-O(2p) states and onset of 3+ valence state of Dy ions. Rietveld Refinment of XRD patterns, Mossbauer spectroscopy and Fe Kedge extended X-ray absorption fine structure measurments show cation reditribution after doping with Dy ions. All the synthesized nanoparticles exhibit ferrimagnetic like behavior. Coercivity increases with Dy doping concentration. Variation of saturation magnetization with Dy concentration is explained on the basis of cation redistribution and size effect. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: MAGNETIC-PROPERTIES; COBALT FERRITE; NIFE2O4 NANOPARTICLES; COFE2O4 NANOPARTICLES; CRYSTAL-STRUCTURE; VALENCE STATE; ANISOTROPY; REFINEMENT; ZINC; NANO